Characterization of learning-to-learn skills in medical students - Yolanda Cabrera Macías; Annia Esther Vizcaíno Escobar; José Aurelio Díaz Quiñones; Ernesto José López González; Ernesto López Cabrera (Medisur)
Foundation: the development of learning-to-learn skills is essential for medical students to ensure their constant self-improvement throughout life. Objective: to characterize the current state of the learning-to-learn development skills in medical students. Methods: the research was developed at the Cienfuegos Medical Sciences University from January 2020 to March 2023, using a mixed research design of the sequential explanatory type. The sample was selected through simple random probabilistic sampling: 255 Medicine degree first-year students, from a universe of 481. To obtain the information, questionnaires, focus groups and observations of teaching activities were used. The processing was carried out using SPSS 26.0 and ATLAS.ti software. Results: Difficulties were obvious in problem-solving skills, planning learning activities and searching for and processing scientific information, as well as in self-regulation and self-assessment of learning processes, in the perception of emotional control and attribution of meaning to learning. Conclusions: Deficiencies were found in the development of learning-to-learn skills in all their dimensions.